Contracts formed by software: An approach from the law of mistake - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2019)
A ‘Contracting Problem’ arises when software is used to autonomously enter into contracts without human input. Questions arise as to how and whether there can be an expression of an objective intention to be legally bound. This article considers three leading solutions to the Contracting Problem. The ‘Mere Tools Theory’, which views software as ‘mere tools’ of communication, is too harsh as it binds users to any software malfunction. The Agency Approach, which treats software as Electronic Agents, capable of contracting on behalf of their users, is untenable as it ascribes unrealistic characteristics to software. The article submits that the optimal solution is to extend the objective theory of contract. Where software produces an unintended consequence, this should be seen as a mistake. An optimal way of risk allocation is for parties to be bound by the representations of their software, unless the other party has knowledge of the mistake.